Redesign of Boiler Heat Recovery Steam Generator (HRSG) on The Utilization of Waste Gas in The Cement Industry - Fiqri Hadi Hendriyansyah; Rifania Nendry W.P.; Vibianti Dwi Pratiwi (Reaktor, 2023)
Approximately, 20%-50% of the total energy consumption during cement production is disposed of unintendedly as waste heat. This is very unfortunate considering that this waste heat still has the energy that can be further utilized. The heat recovery steam generator (HRSG) boiler system is one of widely used solutions in the chemical industry process to save operating costs in the chemical industry process. The purpose of this research is to determine the amount of energy that can be saved by implementing the HRSG system under ideal operating conditions. Based on the simulation results, the HRSG boiler design can produce steam with a temperature of 235°C and subsequently reduce the flue gas temperature from 244°C to 140.6°C. The HRSG system produces energy in the power turbine up to 1,756 kW with total energy exchanged in the system of 17,567.38 kW from the total energy in the flue gas of 20,693.96 kW and provides an overall efficiency of 84.61% at steady state conditions.Keywords: Aspen HYSYS, Waste Heat, Heat Recovery Steam Generator (HRSG)